Duties to refugees, the reluctance of governments, and social science: a Christian perspective. Issue 4 (July 2021) - Young, Alistair
Recent theological discussion of immigration issues, while acknowledging the scriptural mandate of hospitality to migrants, also recognizes that host governments have a duty to protect their borders against those who might cause harm to their citizens. Looking in particular at the special case of refugees, I argue that government policy in many rich European countries, including the UK, falls well short of the hospitality requirement while greatly exaggerating the possibility of harm. I suggest that social science findings on the impact of immigration on host communities provide helpful background for politically engaged Christians who seek to call their governments to account.